Enhanced Surface-and-Interface Coupling in Pd-Nanoparticle-coated LaAlO3/SrTiO3 Heterostructures: Strong Gas- and Photo-Induced Conductance Modulation - Kim, Haeri; Chan, Ngai Yui; Dai, Ji-yan; Kim, Dong-Wook (NATURE PUBLISHING GROUP, 2015)
Pd nanoparticle (NP) coated LaAlO3/SrTiO3 (LAO/STO) heterointerface exhibits more notable conductance (G) change while varying the ambient gas (N-2, H-2/N-2, and O-2) and illuminating with UV light (wavelength: 365 nm) than a sample without the NPs. Simultaneous Kelvin probe force microscopy and transport measurements reveal close relationships between the surface work function (W) and G of the samples. Quantitative analyses suggest that a surface adsorption/desorption-mediated reaction and redox, resulting in a band-alignment modification and charge-transfer, could explain the gas- and photo-induced conductance modulation at the LAO/STO interface. Such surface-and-interface coupling enhanced by catalytic Pd NPs is a unique feature, quite distinct from conventional semiconductor hetero-junctions, which enables the significant conductance tunability at ultrathin oxide heterointerfaces by external stimuli.
Keywords: ELECTRON-GAS; FILMS